FEEDING LOCAL FERMENTED WITH EM-4, AMMONIUM SULFATE, AND UREA ON THE BLOOD FAT LEVEL OF MALE DUCK - Septinova, Dian; Arti, Aisyah Yuli; Sutrisna, Rudy; Tantalo, Syahrio; Hartono, Madi (Jurnal Kedokteran Hewan, 2020)
The objective of this study was to determine the effect of commercial ration by the addition of ammonium sulfate and urea fermented feed ingredients on the blood fat levels of local male ducks. This study used a completely randomized design with 32 male ducks which weredivided into four groups namely R0, R1, R2, R3, and R4. Each group was given the following treatment: R0 only given commercial ration;R1 was given 80% commercial ration + 20% fermentation of EM-4 + 1.5% urea); R2 was given 80% commercial ration + 20% EM-4 + 1.5%ammonium sulfate fermentation; and R3 was given 80% commercial ration + 20% EM-4 + 1.5% urea + 1.5% ammonium sulfate. Variablesin this study were blood fat consisting of cholesterol, triglyceride, High-Density Lipoprotein (HDL), and Low-Density Lipoproteins (LDL).The data obtained were analyzed by using 5% real level and LSD. The results showed that the provision of commercial ration added withlocal feed fermented with ammonium sulfate and urea had a significant effect on cholesterol levels (P0.5), but not significant (P0.05) ontriglyceride, HDL, and LDL levels. Furthermore, the ration that gave the best effect on the blood fat levels of male ducks blood was the ration given to R3 group.